The ethics of sightseeing - MacCannell, Dean (University of California Press, 2011)
Is travel inherently beneficial to human character? Does it automatically educate and enlighten while also promoting tolerance, peace, and understanding? In this challenging book, Dean MacCannell identifies and overcomes common obstacles to ethical sightseeing. Through his unique combination of personal observation and in-depth scholarship, MacCannell ventures into specific tourist destinations and attractions: "picturesque" rural and natural landscapes, "hip" urban scenes, historic locations of tragic events, Disney theme parks, beaches, and travel poster ideals. He shows how strategies intended to attract tourists carry unintended consequences when they migrate to other domains of life and reappear as "staged authenticity". Demonstrating each act of sightseeing as an ethical test, the book shows how tourists can realize the productive potential of their travel desires, penetrate the collective unconscious, and gain character, insight, and connection to the world.